Reliability based design of fluid power pitch systems for wind turbines. Issue 6 (3rd February 2017) - Liniger, Jesper; Soltani, Mohsen; Pedersen, Henrik C.; Carroll, James; Sepehri, Nariman
Abstract: This paper presents a qualitative design tool for evaluation of the risk for fluid power pitch systems. The design tool is developed with special attention to industry standard failure analysis methods and is aimed at the early phase of system design. Firstly, the concept of Fault Tree Analysis is used for systematic description of fault propagation linking failure modes to system effects. The methodology is conducted solely on a circuit diagram and functional behavior. The Failure Mode and Effects Criticality Analysis is subsequently employed to determine the failure mode risk via the Risk Priority Number. The Failure Mode and Effect Criticality Analysis is based on past research concerning failure analysis of wind turbine drive trains. Guidelines are given to select the severity, occurrence and detection score that make up the risk priority number. The usability of the method is shown in a case study of a fluid power pitch system applied to wind turbines. The results show a good agreement to recent field failure data for offshore turbines where the dominating failure modes are related to valves, accumulators and leakage. The results are further used for making design improvements to lower the overall risk of the pitch system. Copyright © 2017 John Wiley & Sons, Ltd.